Pembrolizumab Plus Chemotherapy Versus Chemotherapy Monotherapy as a First-Line Treatment in Elderly Patients (≥75 Years Old) With Non-Small-Cell Lung Cancer - Yang, Zhengyu; Chen, Ya; Wang, Yanan; Hu, Minjuan; Qian, Fangfei; Zhang, Yanwei; Zhang, Bo; Zhang, Wei; Han, Baohui (Frontiers in Immunology, 2022)
Objective: Several trials have shown that pembrolizumab plus chemotherapy was more effective in patients with advanced non-small-cell lung cancer (NSCLC) than chemotherapy monotherapy. However, whether pembrolizumab plus chemotherapy is still a better choice for first-line treatment in elderly patients (≥75 years old) remain unknown. We retrospectively compared the efficacy and safety of these two treatments in elderly patients. Patients and Methods: We collected data of 136 elderly patients with advanced NSCLC who were treated with pembrolizumab plus chemotherapy or chemotherapy monotherapy in our hospital from 2018 to 2020. We compared the progression-free survival (PFS) and overall survival (OS) of patients and analyzed which subgroups might benefit more significantly from pembrolizumab plus chemotherapy. Results: In total population, pembrolizumab plus chemotherapy showed superior PFS and OS than chemotherapy monotherapy (PFS: 12.50 months vs. 5.30 months, P<0.001; OS: unreached vs. 21.27 months, P=0.037). Subgroup analysis showed patients with positive PD-L1 expression, stage IV, good performance score (ECOG-PS <2), fewer comorbidities (simplified comorbidity score <9) or female patients had demonstrated a more evident OS benefit in pembrolizumab plus chemotherapy. In terms of safety, the pembrolizumab plus chemotherapy group had higher treatment discontinuation (26% vs. 5%). Conclusions: Elderly patients using pembrolizumab plus chemotherapy achieved longer PFS and OS, but were more likely to discontinue due to adverse effects, so disease stage, PD-L1 expression, ECOG-PS and comorbidities should be considered when selecting first-line treatment.